Cardiac sarcoidosis: A long term follow up study. - Patrice Cacoub; Catherine Chapelon-Abric; Matthieu Resche-Rigon; David Saadoun; Anne Claire Desbois; Lucie Biard (PLoS ONE, 2020)
Background Prognostic factors are lacking in cardiac sarcoidosis (CS), and the effects of immunosuppressive treatments are unclear. Objectives To identify prognostic factors and to assess the effects of immunosuppressive drugs on relapse risk in patients presenting with CS. Methods From a cohort of 157 patients with CS with a median follow-up of 7 years, we analysed all cardiac and extra-cardiac data and treatments, and assessed relapse-free and overall survival. Results The 10-year survival rate was 90% (95% CI, 84-96). Baseline factors associated with mortality were the presence of high degree atrioventricular block (HR, 5.56, 95% CI 1.7-18.2, p = 0.005), left ventricular ejection fraction below 40% (HR, 4.88, 95% CI 1.26-18.9, p = 0.022), hypertension (HR, 4.79, 95% CI 1.06-21.7, p = 0.042), abnormal pulmonary function test (HR, 3.27, 95% CI 1.07-10.0, p = 0.038), areas of late gadolinium enhancement on cardiac magnetic resonance (HR, 2.26, 95% CI 0.25-20.4, p = 0.003), and older age (HR per 10 years 1.69, 95% CI 1.13-2.52, p = 0.01). The 10-year relapse-free survival rate for cardiac relapses was 53% (95% CI, 44-63). Baseline factors that were independently associated with cardiac relapse were kidney involvement (HR, 3.35, 95% CI 1.39-8.07, p = 0.007), wall motion abnormalities (HR, 2.30, 95% CI 1.22-4.32, p = 0.010), and left heart failure (HR 2.23, 95% CI 1.12-4.45, p = 0.023). After adjustment for cardiac involvement severity, treatment with intravenous cyclophosphamide was associated with a lower risk of cardiac relapse (HR 0.16, 95% CI 0.033-0.78, p = 0.024). Conclusions Our study identifies putative factors affecting morbidity and mortality in cardiac sarcoidosis patients. Intravenous cyclophosphamide is associated with lower relapse rates.